Atrial Fibrillation and Risk of Dementia: Epidemiology, Mechanisms, and Effect of Anticoagulation - Silva, Rose Mary Ferreira Lisboa Da; Miranda, Cláudia Madeira; Liu, Tong; Tse, Gary; Roever, Leonardo (Frontiers in Neuroscience, 2019)
Atrial fibrillation (AF) is one of the cardiovascular risk factors for dementia. Several longitudinal studies have reported an association between AF and dementia independently of stroke history. Although the mechanisms underlying this association are not fully understood, proposed mechanisms include cerebral hypoperfusion, inflammation, genetic factors, cerebral microbleeds, and recurrent silent cerebral ischemia. Oral anticoagulation can be used to minimize risk of cognitive decline and dementia, given that brain insults can be caused by chronic microemboli or microbleeds. However, controversy on the effects of warfarin and direct oral anticoagulants on this risk exists. This article will address these aspects, with data on the studies already published and a critical view on this subject.